KOMPETENSI PENYULUH DALAM MENDUKUNG GERAKAN PEMBERDAYAAN PETANI TERPADU (GPPT) DI KABUPATEN KARANGANYAR - Yuliani Yuliani; Sapja Anantanyu; Agung Wibowo (AGRITEXTS: Journal of Agricultural Extension, 2017)
This study aims to examine the EmpowermentMovement of Integrated Farmers; the extension agents’ competence related with EmpowermentMovement of Integrated Farmers; the factors that affecting the competence of extension agents, to examine the effect of factors that affecting the competence of extension agents with extension agents’ competence. The location of the study was determined purposively because of the presence of EMIF, where the focus of this movement is the empowerment of farmer groups while there are still many farmer groups that are in the beginner class. The population of this research is the extension agents whose working area is in the same sub district with farmers group on the beginner class. The sampling method was done with total sampling is32 people. Data analysis using multiple linear regressions. The extension agents’ competence in compiling the program is low; The extension agents’ competence in preparing the materials, establishing media, agribusiness consulting services, evaluating the implementation of extension, evaluating the impact of extension, conducting the assessment is moderate; The extension agents’ competence in the application of the method is high; (3) Factors that affecting the extension agents’ competence the ability to mobilizing the group (X1); personality (X2); The attitude of extension agents’ (X3); The extension agents’counseling skills (X4); motivation(X6) are moderate; The extension agents’ experience (X5) is very low. (4) There is a significant influence between the counseling skills and the motivation with the extension agents’ competence and there is no significant influence between the ability to mobilizing the group, personality, attitude of extension agents’ and experience with extension agents’ competence.